The current role of MRI in differentiating multiple sclerosis from its imaging mimics - Geraldes, R; Ciccarelli, O; Barkhof, F; De Stefano, N; Enzinger, C; Filippi, M; Hofer, M; Paul, F; Preziosa, P; Rovira, A; De Luca, G; Kappos, L; et al. (Nature Publishing Group, 2018)
MRI red flags proposed over a decade ago by the European Magnetic Resonance Network in MS (MAGNIMS) have guided clinicians in the diagnosis of multiple sclerosis (MS). However, the past 10 years have seen increased recognition that vascular disease can coexist and possibly interact with MS, improvements in the reliability of ways to differentiate MS from novel antibody-mediated CNS disorders (such as anti-aquaporin-4 antibody and myelin-oligodendrocyte glycoprotein antibody-associated diseases) and advances in MRI techniques. In this Review, MAGNIMS updates the imaging features that differentiate the most common mimics of MS, particularly age-related cerebrovascular disease and neuromyelitis optica, from MS itself. We also provide a pragmatic summary of the clinically useful MRI features that distinguish MS from its mimics and discuss the future of nonconventional techniques that have identified promising disease-specific features.